2014
DOI: 10.1371/journal.pone.0114995
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Management Practices That Influence Performance and Welfare of Dairy Calves Reared in Southern Brazil

Abstract: Here we report dairy calf management practices used by 242 smallholder family farmers in the South of Brazil. Data were collected via a semi-structured questionnaire with farmers, inspection of the production environment and an in-depth interview with a sample of 26 farmers. Herds had an average of 22.3 lactating cows and an average milk production of 12.7 L/cow/day. Calves were dehorned in 98% of the farms, with a hot iron in 95%. Male calves were castrated in 71% of the farms; methods were surgery (68%), ema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 62 publications
3
63
1
5
Order By: Relevance
“…Similar to our study, Hotzel et al (2014) reported that most calves were fed with up to 4 l of milk or milk replacer per day, or the equivalent to 10% to 15% of BW. This survey was made from 242 small holder family farms in the South of Brazil.…”
Section: Datasupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our study, Hotzel et al (2014) reported that most calves were fed with up to 4 l of milk or milk replacer per day, or the equivalent to 10% to 15% of BW. This survey was made from 242 small holder family farms in the South of Brazil.…”
Section: Datasupporting
confidence: 88%
“…In Asia and other tropical countries, inadequate heifer management is a main problem for numerous small holder dairy farms (Moran, 2011). In the South of Brazil, 71% of 242 smallholder families reported that diarrhea was the main cause of calf mortality (Hotzel et al, 2014). Santos and Bittar (2015) reported that in three important milk production regions from Brazil almost 48% of all calves present diarrhea and that 22% have respiratory problems.…”
Section: Datamentioning
confidence: 99%
“…Dairy farms often separate calves from their dams within 24 h after birth and then house calves individually (USDA, 2008;Vasseur et al, 2010;Hötzel et al, 2014). Housing milk-fed calves in pairs or groups is increasing in popularity, in part due to the potential of reducing labor requirements per head.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies have reported that sheep and dairy farmers carried out some management practices as part of well establish traditions, rather than following technical knowledge, and do not recognize the need to justify these practices (MoloNy & KENt, 2007;HötzEl et al, 2014). Because some breed standards require that animals be docked, it is clear that these standards are a hindrance to improve sheep welfare.…”
Section: Resultsmentioning
confidence: 99%